INTERNATIONAL TRADE COMPETITIVENESS OF KAZAKHSTANI SMALL AND MEDIUM ENTERPRISES (SMEs) - Aigerim Ashilova; Zhou Xiaochen (Scientific Journal of Pedagogy and Economics, 2020)
Small and medium sized business as an institutional sector of the economy for many years have been dominated by the number and volume of production in the leading countries of the world. Enterprises with a small number of workers provide the flexibility and sustainability of the economic system of the region, brings it closer to the needs of specific consumers and, at the same time, perform an important social role, providing jobs and providing sources of income for a significant number of populations. Although throughout the entire period of the market economy in Kazakhstan, problems of the development of small and medium sized businesses received a lot of attention; including measures such as economic reform, implementation of strategic programs; its social-economic status is still suboptimal. Nevertheless, recent efforts of the state to create a regulatory framework for the support of small and medium sized businesses have not solved the problems of creating a favorable climate for this sector of the economy. The development of small and medium sized businesses, in turn, affects the competitiveness of national market participants at the international level. One of the main tasks in the development of this sphere is the entry of the Kazakhstani market to the international level, increasing its competitiveness. Thus increasing the share of exports of domestic goods to the country’s gross domestic product, as well as the country’s full-fledged transition to a market economy. In this research work, an analysis of doing business in Kazakhstan, prospects for the development of medium and small sized businesses, as well as the level and prospects of competitiveness of domestic entrepreneurs at the international level will be carried out.